2018
DOI: 10.1093/mnras/sty2043
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of hard X-ray spectra of luminous radio galaxies and their radio-quiet counterparts

Abstract: We study the differences in X-ray properties of luminous radio galaxies and their radio-quiet counterparts. In order to avoid biases associated with the dependence of X-ray properties on the black hole mass and Eddington ratio, the radio-loud and radioquiet objects are selected to cover similar ranges of these parameters. Our studies are based on the X-ray data from the Swift/BAT catalogue. We confirm previous results that radio galaxies are on average X-ray-louder than radio-quiet AGNs, but find that their sp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
44
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(55 citation statements)
references
References 84 publications
10
44
1
Order By: Relevance
“…The redshift and Herschel-resolution cuts removed all radio-loud quasars (including FR I and FR II sources) from our sample. This is unsurprising, as such objects are intrinsically rare and tend to be higher redshift; for example, Gupta et al (2018) found that 51/509 (10 per cent) of the overall BAT AGN sample are radio-loud. The large majority of our remaining sources are therefore radioquiet Seyferts.…”
Section: Selection and Properties Of The Jvla 22 Ghz Samplementioning
confidence: 99%
“…The redshift and Herschel-resolution cuts removed all radio-loud quasars (including FR I and FR II sources) from our sample. This is unsurprising, as such objects are intrinsically rare and tend to be higher redshift; for example, Gupta et al (2018) found that 51/509 (10 per cent) of the overall BAT AGN sample are radio-loud. The large majority of our remaining sources are therefore radioquiet Seyferts.…”
Section: Selection and Properties Of The Jvla 22 Ghz Samplementioning
confidence: 99%
“…Starting from the 3CRR catalog 1 , we firstly selected the objects with an available black hole mass estimation, thus the Eddington ratio, which is a key parameter to investigate X-ray properties, can be calculated (e.g., Brandt & Alexander 2015;Gupta et al 2018;Li 2019). The black hole masses in 84 out of the total 173 objects were measured, where all of them were taken from McLure et al (2006) or Buttiglione et al (2010).…”
Section: The Luminous Radio Galaxy Samplementioning
confidence: 99%
“…This seems to indicate that the X-ray emission from jets is important in RLAGNs. However, Gupta et al (2018) recently compiled an excellent sample to investigate the differences of Xray properties between luminous radio galaxies and their radioquiet counterparts, where the black hole mass and Eddington ratio were well selected and the bolometric luminosity were calculated from mid-infrared emission observed by the Wide-field Infrared Survey Explorer (WISE) mission. They argue that the X-ray emission in radio-loud radio galaxies should also come from a disk-corona system because their distribution of the Xray slope is very similar with those of radio-quiet counterparts (see Gupta et al 2018 for details, see also Gupta et al 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover in the NuSTAR observations of AGN populations no links were found between high energy cut-off and Eddington ratio, or BH mass [26,27]. Recent analysis of samples of non-blazar RL and RQ AGN of Swift/BAT catalogue also revealed that the photon indices and high-energy exponential cut-offs of RL and RQ AGN cover the same range of values and do not show significant differences between their distributions [28]. This addresses the questions both about physical conditions causing the cut-off absence in RL AGN or low values of cut-off in RQ ones.…”
Section: Introductionmentioning
confidence: 98%